2016
DOI: 10.1515/aucft-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of nitrogen source for Bifidobacterium bifidum using response surface methodology

Abstract: In order to improve the viable counts of Bifidobacterium bifidum BB01 in the liquid medium, the Central Composite Design (CCD) was used to optimize the nitrogen source in the medium of B. bifidum BB01. The results showed that the nitrogen source composition of B. bifidum BB01 was: peptone 0.9%, yeast extracts 0.3%, beef paste 0.7%. Under the optimal conditions, the viable counts of B. bifidum BB01 reached (2.49±0.06)×109CFU/mL after cultured at 18h, which was 42.97% higher than MRS (lactose), and 12.85% higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The culture conditions for lactic acid bacteria growth are strict and generally require a carbon source, a nitrogen source, inorganic salts, and prebiotics [ 24 ]. These nutrients are not only conducive to the growth of bacteria, but also promote the production of proteases by lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The culture conditions for lactic acid bacteria growth are strict and generally require a carbon source, a nitrogen source, inorganic salts, and prebiotics [ 24 ]. These nutrients are not only conducive to the growth of bacteria, but also promote the production of proteases by lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used is as a leavening agent for dairy products, mainly used for fermented dairy products such as cheese, yogurt, buttermilk, sour cream, etc. And quite a lot of lactic acid bacteria play a beneficial role in human and animal health (Chen et al, 2016). It has been reported that probiotics can maintain the balance of intestinal flora and inhibit pathogenic bacteria, and their mechanism is mainly attributed to the production of acids, hydrogen peroxide, bacteriocins and other substances (Gao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%